VIP activates primordial follicles of rat through ERK-mTOR pathway in tissue culture. Issue 5 (May 2019) - Li, Song; Fan, Qi; Xie, Yanqiu; Lin, Haiyan; Qiu, Qi; Liang, Yihua; Zhang, Qingxue
Abstract : In vitro activation of primordial follicles is becoming more essential in assisted reproductive technologies. Vasoactive intestinal peptide (VIP) is one of the members of the neurotrophin family which has demonstrated to have an impact on follicle development in recent years. This study aims to investigate the effect of VIP on the activation of primordial follicles in neonatal rat in an in vitro culture system and to determine the relevant molecular mechanism of their activation. Ovaries of 4-day-old rats were examined for the expression of VIP receptors and were cultured in mediums containing VIP with or without inhibitors of the ERK–mTOR signalling pathway. They were then collected for histological analysis or measurement of the molecular expression of this pathway. The receptors of VIP were found in granular cells and oocytes of primordial and early-growing follicles in neonatal ovary. The ratio of growing follicle increased in the presence VIP at different concentrations, with the highest level of increase being observed in the 10 −7  mol/L VIP-treated group. The ratio of PCNA-positive granular cells was also increased, while that of the apoptotic oocytes were decreased, and protein analysis showed increased phosphorylation of ERK1/2, mTOR and RPS6 in the VIP-treated group. However, the effect of VIP on the activation of primordial follicle became insignificant with the addition of MEK inhibitor (U0126) or mTORC1 inhibitor (rapamycin). This study indicated that VIP could activate neonatal rat primordial follicle through the ERK-mTOR signalling pathway, suggesting a strategy for in vitro primordial follicle recruitment.